Pirólise flash de diferentes cultivares do capim elefante (Pennisetum purpureum Schum.) - Lessa, Mayara de Oliveira (2019)
Elephant Grass (Pennisetum purpureum Schum.) have high productivity with an annual capacity of the 40 tons of dry matter per hectare, and energy yield up to 25 times greater than the energy consumed this production. In this work, a study was carried out in different cultivars of Elephant Grass, among them, Pennisetum purpureum Schum. cv. Mott (CEM), Pennisetum purpureum Schum. cv. Roxo (CER) and Pennisetum purpureum Schum. cv. Capiaçu (CEC). Biomasses were evaluated terms of the Immediate Analysis, Calorific Power, Elemental Analysis, Structural Composition, Thermogravimetric Analysis, X-Ray Fluorescence (FRX), X-Ray Diffractometry (XRD) and Fourier Transform Infrared Spectroscopy (FTIR), as well as analytical flash pyrolysis at 600 °C in Py-GC / MS and evaluation of the kinetic parameters through thermal analysis. The kinetic parameters of the samples were estimated using non-isothermal methods Flynn-Wall and Model Free Kinetics (Vyazovkin) for the range of holocellulose degradation between 150 to 370 ºC. The methods were well suited to the EMC and CER samples. The volatile compounds produced pyrolysis were mainly oxygenated, including short-chain (C1-C4) compounds, furans, esters, aldehydes, ketones and phenols. The results obtained were similar for the three biomasses with small variations the yields of the pyrolysis products. However, due to its higher height, higher calorific value (16.22 MJ / kg), lower ash content (6.75%), higher volatile content (74.84%) and carbon (42.57%), the CEC has proved the most promising biomass results to be studied for the purpose of energetic application among the other samples.